TANGGUNG JAWAB CAMAT DALAM PEMBUATAN AKTA JUAL-BELI TANAH DALAM KASUS PUTUSAN PENGADILAN NEGERI SUBANG NOMOR 13/PDT.G/2019/ PN SNG. - renny talitha chandra; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
Temporary conveyancer (PPATS) is an officer who helps Indonesian National Land Office (BPN) in making land deeds that should be made by the authorized conveyancer (PPAT), those who have special legal education and are reliable in making land deeds. PPATS is a sub-district head appointed by the minister through BPN because there is a lack of PPAT in certain areas. However, in this case from Subang District Court Decision case number 13/PDT.G/2019/PN.SNG, that there was negligence of the sub-district head, so there was a party with a good faith that suffered loss by the legal acts of the sub-district head. So, it becomes a question that what is the responsibility of the sub-district head in making deed of sale and purchase land in case Subang District Court Decision case number 13/PDT.G/2019/PN.SNG and what is the responsibility of the sub-district head which make one of the party that have a good faith that suffer loss in Subang District Court Decision case number 13/PDT.G/2019/PN.SNG that accordance with applicable law. This research used normative legal research, with the nature of qualitative research with the type of library research. The results of research about how responsibility of sub-district head to do their job as a PPAT with a responsibility and make a deed of sale and purchase land that make a loss to party that have a good faith and about the sufferer party can take a legal action against the sub-district head because of the loss that party got.